Non-viral gene delivery system - Mohamed, Farahidah; Mohd Shafri, Mohd Affendi; Doolaanea, Abd Almonem; Mansor, Nur 'Izzati; Mohd Nor, Nurul Hafizah (2015)
A method of encapsulating one or more nucleic acids such as plasmid dna wherein the nucleic acids are complexed with a cationic surfactant such as CTAB before being encapsulated into particles using a single emulsion solvent evaporation method. (figure 1)